2019
DOI: 10.2166/wh.2019.165
|View full text |Cite
|
Sign up to set email alerts
|

Survey of US wastewater for carbapenem-resistant Enterobacteriaceae

Abstract: A survey for antibiotic-resistant (AR) Escherichia coli in wastewater was undertaken by collecting samples from primary clarifiers and secondary effluents from seven geographically dispersed US wastewater treatment plants (WWTPs). Samples were collected at each WWTP in cool and summer months and cultured using selective media. The resulting isolates were characterized for resistance to imipenem, ciprofloxacin, cefotaxime, and ceftazidime, presence of carbapenemase and extended-spectrum beta-lactamase (ESBL) ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 29 publications
4
22
0
Order By: Relevance
“…e result is comparable to the study done by Petron et al in Morocco, which found a similar finding among Serratia marcescens isolated from water specimens [28]. But this finding is in disagreement with a study conducted in the USA by Hoelle et al, which showed that about 55% of E. coli isolates were positive for VIM gene and 1% were positive for IMP gene [29]. ese variations in the results may be explained by the differences in the time of study and their large sample size.…”
Section: Discussionsupporting
confidence: 51%
“…e result is comparable to the study done by Petron et al in Morocco, which found a similar finding among Serratia marcescens isolated from water specimens [28]. But this finding is in disagreement with a study conducted in the USA by Hoelle et al, which showed that about 55% of E. coli isolates were positive for VIM gene and 1% were positive for IMP gene [29]. ese variations in the results may be explained by the differences in the time of study and their large sample size.…”
Section: Discussionsupporting
confidence: 51%
“…1b), with the exception of December, where the absence of ST131 is likely due to less frequent sample collection during the holiday season. This is in line with other studies that considered seasonality within their data set when detecting E. coli from wastewater (28,29) but in contrast to studies sampling directly from untreated water (30,31), potentially highlighting the efficiency of wastewater treatment plants in maintaining a consistent reduced rate of E. coli from effluent.…”
Section: Resultssupporting
confidence: 88%
“…The presence of CRE in wastewater is a potential concern because this environment may serve as major reservoir leading to HGT events and an increased risk of carbapenem resistance spreading into the environment. The data collected from a recent US survey of seven wastewater treatment plants reported the detection of 20% carbapenem-resistant E. coli isolates of sequence types associated with extra-intestinal infections in humans harboring predominantly bla VIM and bla KPC genes [ 108 ]. Similarly, a study from the United States documented the presence of CRE including E. coli and P. mirabilis isolates harboring bla IMP-27 gene on Inc Q1 plasmids in both environmental and fecal samples of swine production system [ 109 ].…”
Section: Carbapenemases-producing Enterobacteriaceae mentioning
confidence: 99%